Effects of Organized Physical Activity on Selected Health Indices among Women Older than 55 Years - Piotr Zmijewski; Krzysztof Mazurek; Ewa Kozdron; Piotr Szczypiorski; Agata Frysztak (The Scientific World Journal)
The main aim of this study was to determine health benefits among women older than 55 years who participated in organized, group-based physical activity (OPA). Thirty-five women aged 65.0 ± 7.3 years volunteered for this study. The classical and nonclassical cardiovascular (CVD) risk factors were measured before and after a 2-week OPA camp in a remote location and 3 months of OPA. Self-guided physical activity was analyzed 18 months after OPA. Two-week effects included significant decreases in body mass index, waist and hip circumferences, resting systolic and diastolic blood pressure (BP) and resting heart rate, improved exercise capacity (EC), improved low-density lipoprotein and high-density lipoprotein (HDL-C), cholesterol, and other atherogenic lipid indices (ALI), and a reduction in 10-year estimated risk of death from CVD. Three-month effects included a further decrease in systolic BP, improvements in EC and HDL-C, and maintenance of lower levels of ALI, as well as lower CVD risk. The implementation of the OPA programme had a positive impact on somatic features, exercise capacity, biochemical indices, and risk for death from CVD. The presented programme can be regarded as an effective element of primary prevention of cardiovascular diseases among women older than 55 years.